Advanced electronic packaging (Wiley ; Piscataway, 2006)
This updated edition of the widely adopted industry classic Advanced Electronic Packaging, Second Edition now features a new focus on the current practices in electronic packaging. Since electronic packaging is a constantly and rapidly changing field, there is a continuing need to educate students, not only on the fundamentals of packaging, but also on current and future technologies. Much of the material contained in the first edition of the book, primarily the background material, has been transferred directly to the second edition